Determinacion de un patron heterotico a partir de la evaluacion de un dialelo de diez lineas de maiz subtropical - Gonzalez, S.=700 1 Cordova, H.; Rodriguez, S.; De Leon, H.; Serrato, V.M.
(En, Es)
ilus., 9 ref.
Keywords: ZEA MAYS; FITOMEJORAMIENTO; HIBRIDACION; VIGOR HIBRIDO; COSTA RICA